GRANULOMATOUS MASTITIS: A REVIEW OF 14 CASES - Ahmed, Rubab; Sultan, Faisal (Journal of Ayub Medical College Abbottabad, 2006)
Background: Tuberculosis of breast is a rare entity and may be confused with carcinoma of the breast. We present a case series of 14 patients with granulomatous mastitis, seen over a seven-year period from a cancer centre in Lahore, Pakistan. Methods: The cases were retrieved using electronically coded records and clinical, radiological and pathological data reviewed. Cases with a histologic diagnosis of granulomatous mastitis were included. Results: Granulomatous mastitis was seen at a frequency of 0.37% of the 3768 patients seen with breast diseases (3722 women; 46 men) during this time period. The average age at presentation was 40.7 years [range 14- 65 years]. The most common presentation was a lump in the upper outer quadrant of the breast. Mammography showed a range of appearances. Diagnosis was obtained via fine needle aspiration (10 cases), core biopsy (2 cases) and excision (2 cases). Acid-fast bacilli were seen in five out of the 14 patients. Ten out of 14 patients completed treatment at our centre with satisfactory response. Conclusions: Granulomatous mastits is an uncommon disease and typically presents with a lump in the breast. The diagnosis can be established by fine needle cytology in the majority of cases. Acid-fast bacilli are seen a minority of the cases. Key words: granulomatous inflammation, mastitis, breast, tuberculosis, Pakistan.